Shock & vibration, aircraft/aerospace, energy harvesting, acoustics & optics. Volume 9 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Harvie, Julie M.; Baqersad, Javad (Conference proceedings of the Society for Experimental Mechanics series., 2017)
Shock & Vibration, Aircraft/Aerospace and Energy Harvesting, Volume 9: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the ninth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Shock & Vibration, Aircraft/Aerospace and Energy Harvesting including papers on: Shock & Vibration Testing Aircraft/Aerospace Applications Optical Techniques: Digital Image Correlation Vibration Suppression & Control Damage Detection Energy Harvesting.